Damage‐Free Depth Profiling of Electronic Structures in Multilayered Organic Semiconductors by Photoelectron Spectroscopy and Cluster Ion Beam. Issue 11 (6th September 2021) - Hu, Juntao; Wang, Dengke; Li, Peicheng; Chen, Nan; Zhang, Tao; Wu, Yan; Wu, Di; Zhao, Yongbiao; Zhu, Qiang; Fu, Zewei; Lu, Zheng-Hong
Abstract : The chemical and electronic properties of multilayers are known to dictate the performance of organic semiconductor devices. Gas cluster ion beam (GCIB) is developed for removing layer‐by‐layer molecular materials from surfaces. It is, however, not clear whether GCIB sputter can leave a damage‐free surface so that the true chemical and electronic properties can be measured. Herein, X‐ray and ultraviolet photoelectron spectroscopy (XPS and UPS) are used to probe the chemical and electronic structures of organic semiconductors bombarded by GCIB. It is found that the highest occupied molecular orbitals (HOMOs) measured by UPS are very sensitive to ion‐beam bombardment, whereas the XPS‐measured core levels show little change. It is, therefore, essential to use UPS for determining whether the chemical and electronic properties are damaged. Of all combinations of cluster size and beam energy, it is found that 4 keV 2000 argon ion cluster can produce a fresh damage‐free organic surface. Applying this optimal beam to sputter stacked films comprising tris(8‐hydroxy‐quinoline) aluminum (Alq3 )/ N, N′ ‐bis‐(1‐naphthyl)‐ N, N′ ‐diphenyl‐1, 1 ′ ‐biphenyl‐4, 4 ′ ‐diamine (NPB)/Alq3, it is shown that the chemical and electronic structures of the buried interfaces can be measured. This work demonstrates that photoelectron spectroscopies combined with GCIB can be used to construct chemical and electronic structures of multilayers in organic devices. Abstract : Traditional method of using core levels to evaluate ion beam damages is shown to be misleading. Examining valence band structure is key to optimizing ion beams for damage‐free stripping of molecules from film surfaces. With optimized argon ion cluster beam, photoelectron spectroscopies can be used to measure chemical and electronic structures of various functional layers in semiconductor devices.